2009
DOI: 10.1186/2047-783x-14-12-507
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of chronic hepatitis C virus infection in HIV co-infection

Abstract: Chronic HCV co-infection is present in up to one third of HIV-positive patients in Europe. In recent years, apart from the traditional transmission route of intravenous drug abuse, outbreaks of sexually transmitted acute HCV infections, mainly among HIV-positive men who have sex with men, have contributed to the overall disease burden.Because the natural course of HCV infection is substantially accelerated in HIV-co-infection, end-stage liver disease has become the most frequent cause of non-AIDS related death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…[ 11 13 ] In the interferon (IFN) treatment era, a minority of individuals could be treated due to the occurrence of significant adverse effects and low sustained virological response (SVR) rates. [ 12 , 14 , 15 ] With DAAs, especially IFN-free regimens, HCV therapy has been simplified and coinfected patients have achieved high cure rates. [ 11 , 12 ] Randomized clinical trials and real-life studies in different parts of the world have shown SVR rates greater than 90% in patients with HCV/HIV, similar to that reported for patients without HIV coinfection.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 13 ] In the interferon (IFN) treatment era, a minority of individuals could be treated due to the occurrence of significant adverse effects and low sustained virological response (SVR) rates. [ 12 , 14 , 15 ] With DAAs, especially IFN-free regimens, HCV therapy has been simplified and coinfected patients have achieved high cure rates. [ 11 , 12 ] Randomized clinical trials and real-life studies in different parts of the world have shown SVR rates greater than 90% in patients with HCV/HIV, similar to that reported for patients without HIV coinfection.…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests, however, that people infected with HIV seem less likely to eradicate the infection spontaneously, compared to HIV negative individuals with reported clearance rates varying widely from 4-26 %. 3,42,[44][45][46][47][48][49][50] Because acute symptomatic hepatitis C infection is correlated to higher spontaneous viral clearance rates, this patient was closely observed for spontaneous viral clearance before treatment was considered. However, with a recurrent flare of his serum aminotransferase levels and HCV viral load 5 weeks after discharge, it was felt that his chance of achieving spontaneous viral clearance was low.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between treatment for hepatitis C and other treatments are common and can worsen the side effects. In patients co‐infected with HCV and HIV, drug–drug interactions and cumulative toxicity between nucleoside analogues and anti‐HCV therapy have been described, including hepatic decompensation (sometimes fatal) in patients with cirrhosis [8].…”
Section: Discussionmentioning
confidence: 99%
“…Interactions with other therapies are also common and can worsen side effects. For example, cumulative toxicity and drug–drug interactions have been observed in patients receiving peginterferon alfa/ribavirin therapy for hepatitis C and nucleoside analogues for coinfection with human immunodeficiency virus (HIV) [8]. However, an extensive literature search did not identify reports of a drug interaction between ribavirin and the neuraminidase inhibitor oseltamivir.…”
Section: Introductionmentioning
confidence: 99%